The Leadership Role Of The Village Head In Realizing Development In Tetehosi I Village, Gunungsitoli Idanoi Sub-District In 2023 - Evi Astuti Harefa; Adrianus Bawamenewi; Amstrong Harefa (Universitas Muhammadiyah Enrekang, 2023)
Leadership can be defined as an individual's ability to influence, motivate and enable others to contribute to the effectiveness and success of the Village. The essence of national development is basically the human being himself who is the center point of all development efforts and what will be built. Article 26 paragraph (2) of Law No. 6 of 2014 states that the Village Head is in charge of organizing the Village administration, implementing Village development, fostering the Village community and empowering the Village community. This research aims: To describe the leadership role of the Village head in realizing development in Tetehosi I Village, Gunungsitoli Idanoi District in 2023. The research method used in this research is a qualitative method with a descriptive approach. The data collection techniques used are observation, interview, and documentation techniques. The results of this study reveal that the leadership role of the Village Head in realizing development in Tetehosi I Village is: being a facilitator of planned development, being a mobilizer to mobilize Village officials and the community, being a motivator to achieve a goal, running in accordance with established regulations. The constraints faced in realizing development are: first, budget absorption; this is related to the allocation of Village development because the Village has three Hamlets and a very large population of Tetehosi I with a total of 2,238 residents; second, not all community aspirations can be facilitated; third, Village funds in Tetehosi I are very limited (Village funds are not focused on development alone); fourth, lack of community participation; fifth, there are differences of opinion regarding the land / plot being built and lack of cohesiveness between communities. The efforts made by the Village Head in this case are the Village Head in carrying out his role as a facilitator, mobilizer and motivator, being a leader for the Village apparatus team, accepting all ideas or aspirations from various elements of the community; bringing the community closer if there are residents who have different assumptions or disputes during the course of development.